High temperature friction and wear of atmospheric plasma spray deposited NiMoAl-Ag-WS2 composite coatings - Singh A.K.; Atheaya D.; Tyagi R.; Ranjan V. (My University, 2025)
Tribological performance of atmospheric plasma sprayed NiMoAl, NiMoAl-10 wt% Ag, NiMoAl-10 wt% WS2 and NiMoAl-5 wt% Ag-5 wt% WS2 composite coatings has been evaluated by carrying out uni-directional sling wear tests against Al2O3 ball at a fixed load and sliding speed of 5 N and 0.35 m/s at temperatures ranging from RT to 800 °C. The hardness of basic NiMoAl coating has been found to decrease from 415 HV0.2 to 355 HV0.2 with the addition of 10 wt% silver and to 400 HV0.2 after adding both Ag (5 wt%) and WS2 (5 wt%). However, the hardness has been found to increase from 415 HV0.2 to 440 HV0.2 with addition of 10 wt% WS2. Both the coefficient of friction and the wear rate decreased significantly with addition of solid lubricant in NiMoAl coating at all the temperatures from 25 °C to 800 °C. However, the composite coating containing a combination of Ag and WS2 resulted in the lowest coefficient of friction and wear rate among all the coatings at all the temperatures highlighting thus the ability of Ag and WS2 to work in a synergistic manner in achieving low friction and wear. The coefficient of friction for NiMoAl-Ag-WS2 coating decreased continuously from 0.32 to 0.16 with the increasing temperature from 25 °C to 800 °C. The improvement in tribological performance has been attributed to the formation of lubricious oxides viz. NiO, NiMoO4, MoO3, WO3 etc. and silver molybdates like Ag2Mo2O7, Ag2MoO4, Ag2Mo4O13 by tribo-chemical reaction at elevated temperatures. © 2022